Identification of Language Attitude by Non-Natives Towards Madurese Language in UTM - Afidha, Chindy; Halili, Mohammad (Edu-Ling: Journal of English Education and Linguistics, 2024)
The objectives of this research are to identify the language attitudes towards the Madurese language depicted by non native students in Universitas Trunojoyo Madura (UTM) and whether sex differences carry an impact on their attitudes. This research employed an online survey to the targeted participants. They were simply required to respond to the questionnaire designed using Likert Scale.  The sample of this research the answers of the questionnaire obtained. The data were gathered by using Google Form and were analyzed by using qualitative method. The results showed that there were only 2 statements who get a positive attitude towards Madurese language and the remaining 7 statements revealed they get a negative attitude. It also displayed that female respondents have more motivation for Madurese to be as popular as Javanese, contrary to males. What we can suggest from the current research is to have further research accommodating more participants.